Seven tesla MRI improves detection of focal cortical dysplasia in patients with refractory focal epilepsy. Issue 2 (10th February 2017) - Veersema, Tim J.; Ferrier, Cyrille H.; van Eijsden, Pieter; Gosselaar, Peter H.; Aronica, Eleonora; Visser, Fredy; Zwanenburg, Jaco M.; de Kort, Gerard A. P.; Hendrikse, Jeroen; Luijten, Peter R.; Braun, Kees P. J.
Summary: Objective: The aim of this study is to determine whether the use of 7 tesla (T) MRI in clinical practice leads to higher detection rates of focal cortical dysplasias in possible candidates for epilepsy surgery. Methods: In our center patients are referred for 7 T MRI if lesional focal epilepsy is suspected, but no abnormalities are detected at one or more previous, sufficient‐quality lower‐field MRI scans, acquired with a dedicated epilepsy protocol, or when concealed pathology is suspected in combination with MR‐visible mesiotemporal sclerosis—dual pathology. We assessed 40 epilepsy patients who underwent 7 T MRI for presurgical evaluation and whose scans (both 7 T and lower field) were discussed during multidisciplinary epilepsy surgery meetings that included a dedicated epilepsy neuroradiologist. We compared the conclusions of the multidisciplinary visual assessments of 7 T and lower‐field MRI scans. Results: In our series of 40 patients, multidisciplinary evaluation of 7 T MRI identified additional lesions not seen on lower‐field MRI in 9 patients (23%). These findings were guiding in surgical planning. So far, 6 patients underwent surgery, with histological confirmation of focal cortical dysplasia or mild malformation of cortical development. Significance: Seven T MRI improves detection of subtle focal cortical dysplasia and mild malformations of cortical development in patients with intractable epilepsy and may therefore contribute to identification of surgical candidates and complete resection of the epileptogenic lesion, and thus to postoperative seizure freedom.